(untitled) (Italian Review of Legal History, 2024)
This essay reconstructs the history of the trials held for the Piazza della Loggia massacre – 28 May 1974, eight dead and over a hundred injured – linked – like others between 1969 and 1980 – to the strategy of tension. At the time of the Cold War, for fear of communism in power also in Italy, the Services opposed political-military secrecy to the investigators, sidetracked the investigations, delayed by decades the conviction of those responsible, material perpetrators, supporters, instigators; many remained unpunished. In those years the judiciary and legal culture sensed a field of tension between the logic of the criminal trial, intended to ascertain the responsibility of the individual defendants, and the historical truth, even beyond the procedural ‘constraints’. The judge became ‘historian’; the ruling of 22 July 2015 of the Court of Assizes of Appeal of Milan considered the results of the same trial as “evidence” and placed the massacre in its «context». The search for the ‘why’ of the massacres led to the ‘who’, in the «historical-political context, but also in the judicial one»; on 20 June 2017 the Court of Cassation confirmed the trial strategy, making definitive the convictions of Carlo Maria Maggi – the undisputed ‘leader’ of Ordine Nuovo – and Maurizio Tramonte – a collaborator of the Services – at the time exponents of the «radical right of subversive origin».